2006
DOI: 10.1007/s10444-004-7626-z
|View full text |Cite
|
Sign up to set email alerts
|

An explicit second order spectral element method for acoustic waves

Abstract: The acoustic wave equation is here discretized by conforming spectral elements in space and by the second order leap-frog method in time. For simplicity, homogeneous boundary conditions are considered. A stability analysis of the resulting method is presented, providing an upper bound for the allowed time step that is proportional to the size of the elements and inversely proportional to the square of their polynomial degree. A convergence analysis is also presented, showing that the convergence error decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 27 publications
5
16
0
Order By: Relevance
“…Figure 4 shows the numerical error against the size of the mesh h ¼ h coarse . We found that, for q ¼ 2 and 4, the convergence rate is of order three, in agreement with the theoretical estimates (Zampieri and Pavarino, 2006;Grote and Schötzau, 2009). Figure 5 displays the recorded signal at one of the receiver's position.…”
Section: Local Time Steppingsupporting
confidence: 88%
“…Figure 4 shows the numerical error against the size of the mesh h ¼ h coarse . We found that, for q ¼ 2 and 4, the convergence rate is of order three, in agreement with the theoretical estimates (Zampieri and Pavarino, 2006;Grote and Schötzau, 2009). Figure 5 displays the recorded signal at one of the receiver's position.…”
Section: Local Time Steppingsupporting
confidence: 88%
“…We consider the use of a control algorithm to solve the time-harmonic acoustoelastic problem in the domain Ω ⊂ R 2 , which is divided into the solid part Ω s and the fluid part Ω f by the interface Γ i (see Figure 1). Instead of solving directly the time-harmonic equation, we return to the corresponding time dependent equation (see, e.g., [17,10]) and look for time-periodic solution. The convergence is accelerated with a control technique by representing the origi-nal time-harmonic equation as an exact controllability problem [18,19] for the time dependent wave equation…”
Section: Mathematical Modelmentioning
confidence: 99%
“…For space discretization, we use the spectral elements method (see, e.g., [24,17,6,10]), which is based on the weak formulation of the system (1)- (8). That is why we introduce the function spaces…”
Section: Spatial Discretizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[38]) Suppose that u ∈ C 2 (0, T; H s (Ω)) ∩ C 4 (0, T; L 2 (Ω)) is the exact solution of M u n+1 -2u n + u n-1 k Su n = 0 and U is the approximation result of the spectral element method under stability conditions on k. Then, for all t n > 0, we have u(t n ) -U n L 2 (Ω) ≤ O h min(N,s) N -s + k 2 .…”
mentioning
confidence: 99%